MIXED SPEECH OF AN EARLY BILINGUAL CHILD: A CASE STUDY ON JAVANESE-INDONESIAN BILINGUALISM - Fauziati, Endang (Universitas Muhammadiyah Surakarta, 2008)
The present study is concerned with mixed languages in the speech of a bilin- gual child, in Indonesian and Javanese. It is a cross-sectional study. The data of this study are in the form of sentences containing mixed languages. There are 50 sentences used as the data that are collected through observation and note taking. The collected data are then analyzed using descriptive method. The data analysis has revealed that the childâs speech does contain elements from both languages: Indonesian and Javanese. The language mixing occurs at mostly all linguistic lev- els. The syntax, the morphology, and lexicon are formed or taken from both lan- guages. The analysis also reveals that the child is still at the initial level of a bilin- gual. He has one lexical system with words from both languages. He also uses a mixed syntactical system. Both are evidence that he is a simultaneous bilingual, a bilingual from the start. Such language mixing is so common among normal bilinguals. A child who grows up simultaneously learning two or more languages usually goes through such a phase. This also makes possible that the child has been exposed to a mixed language input.Â Key Words: Bilingual children, language mixing, mixed languages.